Solitary thoracic osteochondroma presenting as Brown-Séquard syndrome - Ramdasi, Raghvendra Vijayrao (BMJ Case Rep, 2014)
We discuss a rare case of solitary osteochondroma arising from D2–D3 vertebrae presenting as Brown-Séquard syndrome (BSS) in a 28-year-old man following a fall. MRI revealed cord compression by an extradural ventrolateral tumour projecting into the spinal canal at D2–D3 level. Intraoperatively, it was found to be a bony tumour arising from the left of the D2 and D3 vertebral bodies, left pedicles and adjacent articular facets. The neurological deficits of the patient improved after the surgery.